Effect of Organizational Culture, Mobbing, Organizational Justice, and Professional Attitude Towards Hospital Nurse Work Performance - Hans Christian O; Yohana F; Cahya Palupi Meilani (Budapest International Research and Critics University, 2022)
This study aims was to see the effect of organisational culture, mobbing, organisational justice, and professional attitude on thethe performance of nurses at XYZ Hospital. This research was conducted at XYZ Hospital in Jakarta City. The population in this study were 160 nurses who worked for at least one year at XYZ Hospital. The sampling technique was determined by using the purposive sampling method. PLS-SEM data analysis technique using analysis software SmartPLS version 3.0. The results of this study indicate that H1 professional attitude has a positive and significant effect on performance. H2 mobbing has a negative and significant effect on performance. H3 organisational justice has a positive and significant effect on performance. H4 organisational culture has a positive and significant effect on performance.